Analysis of Walet Business Revenue in Ambarawa Village Batu Ampar District Kubu Raya Regency - Devi Triana; Mashudi Mashudi; F.Y Khosmas (Jurnal Riset Ekonomi dan Akuntansi, 2025)
The swallow nest business in Ambarawa Village is growing, supported by the availability of large land and high demand for local and export markets. Although it is a side job, this business has great potential to increase income if managed well and supported by knowledge of proper maintenance techniques. This study aims to analyze the clarity of the capital used in the construction of the swallow house, the income of swallow entrepreneurs at each harvest, and the obstacles faced by swallow entrepreneurs. The population of this study consisted of 32 swallow entrepreneurs in Ambarawa Village with a sample of 15 entrepreneurs who had produced swallow nest harvests. The study used a qualitative descriptive method through direct communication techniques, observation, and documentation studies, as well as tools in the form of interview guidelines, observation sheets, and documentation. The results of the study showed that the capital for the swallow nest business varied, ranging from IDR 120,000,000 to IDR 370,000,000. The net income of swallow entrepreneurs also varied, ranging from IDR 4,550,000 to IDR 28,500,000 per month. The highest income reached Rp28,500,000, while the lowest income was Rp4,550,000. Swiftlet entrepreneurs face various obstacles, such as unstable weather, pests (cockroaches, birds, rats, and geckos), difficulty in obtaining building materials due to rural locations, uneven distribution of swiftlets, lack of assistance or counseling from the government, and declining prices of swiftlet nests.